EKSISTENSI TATANAN PERKAWINAN SEDULUR SIKEP (MASYARAKAT SAMIN) DUKUH BOMBONG DI ERA GLOBALISASI - Seytaningrum, Dewi (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
Samin community in Dukuh Bombong still mantain and practice Samin’s rule in their daily life. Rapid flow of globalization, does not rule out the possibility that the teachings Samin’s shifted. The purposes of this research are to analyze the existence of marriage order Samin community in the era of globalization. The research uses the qualitative method and the ethnography approach. Method of collecting data in this research is deep interview, observation, and documentation. The result of the research shows Samin community in Dukuh Bombong still maintain the marriage order according to their teachings. The Samin community in Dukuh Bombong married without involving the government, such as KUA (Office of Religious Affairs), village apparatus. The marriage stages of Samin community, including shortening, nyuwito, rukunan/seksenan. The Samin community in Dukuh Bombong are more open about marriage customs only on the affairs of choosing a spouse.Keywords: Samin community, marriage